2018
DOI: 10.1140/epjc/s10052-017-5484-3
|View full text |Cite
|
Sign up to set email alerts
|

Temperature quenching in LAB based liquid scintillator

Abstract: The effect of temperature changes on the light output of LAB based liquid scintillator is investigated in a range from −5 to 30 • C with α-particles and electrons in a small scale setup. Two PMTs observe the scintillator liquid inside a cylindrically shaped aluminum cuvette that is heated or cooled and the temperature dependent PMT sensitivity is monitored and corrected. The α-emitting isotopes in dissolved radon gas and in natural Samarium (bound to a LAB solution) excite the liquid scintillator mixtures and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
2
4
0
1
Order By: Relevance
“…The light yield of Linear Alkylbenzene (LAB) based LS was found to increase ∼ 0.3% per degree in average from room temperature to -40 • C [15]. A similar result was also reported in another study from 30 • C to -5 • C [16]. However, all these studies focus on reducing thermal quenching, thus increasing the light yield of LS, with small samples.…”
Section: Introductionsupporting
confidence: 78%
“…The light yield of Linear Alkylbenzene (LAB) based LS was found to increase ∼ 0.3% per degree in average from room temperature to -40 • C [15]. A similar result was also reported in another study from 30 • C to -5 • C [16]. However, all these studies focus on reducing thermal quenching, thus increasing the light yield of LS, with small samples.…”
Section: Introductionsupporting
confidence: 78%
“…Additionally, the quenching of the scintillator cocktail has a temperature dependence that varies based on the particle type [28]. These measurements have been corroborated through multiple other studies [29,30].…”
Section: Quenchingsupporting
confidence: 62%
“…Recent measurements of the Birks' constant are in the range of 0.0066 ± 0.0016 to 0.0076 ± 0.0003 cm/MeV for -particles [24], 0.0094 ± 0.0002 to 0.0098 ± 0.0003 cm/MeV for protons [25], and ∼ 0.0074 cm/MeV for electrons [26]. Additionally, the quenching of the scintillator cocktail has a temperature dependence that varies based on the particle type [27]. These measurements have been corroborated through multiple other studies [28,29].…”
Section: Quenchingmentioning
confidence: 99%
“…No timing information has been used and more sophisticated spatial reconstruction techniques could likely improve the e − vs. γ separation further. [18]. The measurements from the prototype obtained with the opaque formulations are compared with those from the transparent scintillator (red), which serves as a control sample.…”
Section: Liquido's Novel Detection Techniquementioning
confidence: 99%
“…The high (dark blue) and low (light blue) opacity formulations are obtained by mixing in a paraffin polymer at 10% and setting the temperature at 12 • C and 26 • C, respectively. Studies of an LAB-based scintillator showed only percent-level effects on the light yield from a similar temperature change[18]. The measurements from the prototype obtained with the opaque formulations are compared with those from the transparent scintillator (red), which serves as a control sample.…”
mentioning
confidence: 99%